Minor Prime Factorization for n-D Polynomial Matrices over Arbitrary Coefficient Field - Jinwang Liu; Dongmei Li; Licui Zheng (Complexity)
In this paper, we investigate two classes of multivariate (n-D) polynomial matrices whose coefficient field is arbitrary and the greatest common divisor of maximal order minors satisfy certain condition. Two tractable criterions are presented for the existence of minor prime factorization, which can be realized by programming and complexity computations. On the theory and application, we shall obtain some new and interesting results, giving some constructive computational methods for carrying out the minor prime factorization.